2020
DOI: 10.21511/imfi.17(4).2020.32
|View full text |Cite
|
Sign up to set email alerts
|

Unobservable characteristics of board directors and the performance of financial services firms in Nigeria

Abstract: This paper examines the intricate link between unobservable characteristics of directors on the corporate board and firm performance. It aims to extend the literature on corporate governance and firm strategic performance from the perspective of emerging African economies. A mix of performance measures were used (Tobin Q, return on assets, and share price) and unobservable characteristics were captured as a stochastic element or heterogeneity of observable board characteristics (board activity, gender diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…It showed that continuous quality improvement (CQI), leadership (LDS), employees' involvement (EMI), benchmarking (BMG) and customer relationship management (CRM) significantly correlate with organizational performance (OGP) of microfinance banks. Since none of the coefficients of the independent variables exceed 0.9, there was an absence of multi-collinearity (Osazevbaru & Tarurhor, 2020).…”
Section: B Correlation Analysismentioning
confidence: 99%
“…It showed that continuous quality improvement (CQI), leadership (LDS), employees' involvement (EMI), benchmarking (BMG) and customer relationship management (CRM) significantly correlate with organizational performance (OGP) of microfinance banks. Since none of the coefficients of the independent variables exceed 0.9, there was an absence of multi-collinearity (Osazevbaru & Tarurhor, 2020).…”
Section: B Correlation Analysismentioning
confidence: 99%